Personalized support for chronic conditions - Lasorsa, Irene; D’Antrassi, Pierluigi; Ajčević, Miloš; Stellato, Kira; Di Lenarda, Andrea; Marceglia, Sara; Accardo, Agostino (Applied Clinical Informatics, 2016)
Solutions for improving management of chronic conditions are under the attention of healthcare systems, due to the increasing prevalence caused by demographic change and better survival, and the relevant impact on healthcare expenditures. The objective of this study was to propose a comprehensive architecture of a mHealth system aimed at boosting the active and informed participation of patients in their care process, while at the same time overcoming the current technical and psychological/clinical issues highlighted by the existing literature.After having studied the current challenges outlined in the literature, both in terms of technological and human requirements, we focused our attention on some specific psychological aspects with a view to providing patients with a comprehensive and personalized solution. Our approach has been reinforced through the results of a preliminary assessment we conducted on 22 patients with chronic conditions. The main goal of such an assessment was to provide a preliminary understanding of their needs in a real context, both in terms of self-awareness and of their predisposition toward the use of IT solutions.According to the specific needs and features, such as mindfulness and gamification, which were identified through the literature and the preliminary assessment, we designed a comprehensive open architecture able to provide a tailor-made solution linked to specific individuals’ needs.The present study represents the preliminary step towards the development of a solution aimed at enhancing patients’ actual perception and encouraging self-management and selfawareness for a better lifestyle. Future work regards further identification of pathology-related needs and requirements through focus groups including all stakeholders in order to describe the architecture and functionality in greater detail.Citation: Lasorsa I, D’Antrassi P, Ajčević M, Stellato K, Di Lenarda A, Marceglia S, Accardo A. Personalized support for chronic conditions: a novel approach for enhancing self-management and improving lifestyle
Keywords: Patients with chronic illness or special needs; mHealth; mindfulness; decision support system; patient self-care; home care and e-health